Numerical Analysis of the Effect of Adding Bamboo Culms on Hollow Composite Concrete Column Structures on Axial Capacity - Muhtadi, Sabilul; Umniati, B. Sri; Sulton, Mohammad (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2022)
The problem of self-weight in a structure is an important thing to study. This study aims to find a solution to the problem of self-weight by making a hollow column structure. Bamboo is added to the column structure to replace the strength of the concrete volume lost due to voids. The test object consisted of four columns, three hollow columns with the addition of bamboo rods, and one solid column. Variations in the number of bamboo sticks, namely one, two, and four sticks, were inserted into a column with a cross-section of 300x300 mm and a height of 800 mm. The type of bamboo used is petung bamboo with a minimum age of three years with a diameter of ±120 mm. Twelve pieces of bamboo reinforcement measuring 15x10 mm and four pieces of steel reinforcement with a diameter of 10 mm were used as the primary reinforcement. For stirrups, closed stirrups with a diameter of 8 mm are used. The load given to the column is an axial load of 900 kN on the top surface of the column. From the results of the study, the presence of cavities and the addition of bamboo stems in the column caused an increase in the value of the axial deformation, from 0.2675 mm in the Solid Column, then Columns A, B, and C increased to 0.2707 mm, 0.2731 mm and 0.2874 mm respectively.ABSTRAKPermasalahan berat sendiri pada suatu struktur menjadi hal yang penting untuk dikaji. Penelitian ini bertujuan untuk menemukan solusi dari permasalahan berat sendiri dengan membuat struktur kolom berongga. Untuk menggantikan kekuatan dari volume beton yang hilang karena rongga, maka ditambahkan bambu ke dalam struktur kolom. Benda uji terdiri dari empat kolom, tiga kolom berongga dengan penambahan batang bambu dan satu kolom solid. Variasi jumlah batang bambu yaitu satu, dua, dan empat batang,  dimasukkan ke dalam kolom dengan penampang 300x300 mm dan tinggi 800 mm. Jenis bambu yang digunakan yaitu bambu petung berumur minimal tiga tahun dengan diameter ±120mm. 12 buah tulangan bambu berukuran 15x10 mm dan 4 buah tulangan baja berdiameter 10 mm digunakan sebagai tulangan utama. Untuk sengkang, digunakan sengkang tertutup dengan diameter 8 mm. Beban yang diberikan pada kolom berupa beban aksial sebesar 900 kN pada permukaan atas kolom. Dari hasil penelitian, adanya rongga dan penambahan batang bambu pada kolom menyebabkan kenaikan nilai deformasi aksial, dari 0,2675 mm pada Kolom Solid, lalu Kolom A, B dan C berturut-turut meningkat menjadi 0,2707 mm, 0,2731 mm dan 0,2874 mm.